Functional activity of the monocyte immune link in gastric adenocarcinoma - O. V. Smirnova; E. S. Ovcharenko (Медицинская иммунология, 2023)
Stomach cancer is in the top ten in terms of prevalence and ranks 4th in terms of causes of death worldwide. The most common and most aggressive variant of gastric cancer is adenocarcinoma. The monocytic link of immunity provides the main line of the body's fight against malignant cells, while in patients with adenocarcinoma it is insufficiently studied. The purpose of the study was to evaluate the functional activity of monocytes in patients with gastric adenocarcinoma at different stages of the disease.Individuals (n = 164) were examined, among whom 85 were diagnosed with stage I-IV stomach adenocarcinoma. The study also involved 79 apparently healthy donors. The functional activity and oxygen-dependent phagocytosis of monocytes were assessed by the chemiluminescent method. Luminol was used as a chemiluminescence inducer. The respiratory burst was activated with opsonized zymosan.In patients with stomach adenocarcinoma, at rest (spontaneous chemiluminescence), an increase in the time the curve reached the maximum intensity of chemiluminescence (Tmax = 7957 s), the area under the chemiluminescence curve (Squr = 0.2 x 106), the activation index (1.89 c. u.) and a decrease in the maximum value of chemiluminescence intensity (Imax = 424 c. u.) relative to the control group (Tmax = 5533 s, Squr = 0.011 x 106, activation index = 0.88 c. u., Imax = 424 c. u., p < 0.05) were seen. When chemiluminescence is induced in patients with stomach adenocarcinoma, a statistically significant predominance of Squr is fixed (0.46 x 106, in the control group Squr = 0.031 x 106). Also, in the group of patients with stomach adenocarcinoma, monocytic phagocytosis was reduced by more than 2 times (29% vs 84% in the control group, p < 0.05). When analyzing the studied parameters, depending on the stage of the disease, it was found that the violation of the chemiluminescent reaction in patients with stomach adenocarcinoma is fixed already at an early stage. At the same time, in patients with stage IV stomach adenocarcinoma, the indicators of spontaneous and induced chemiluminescence are more than 2 times different from those in the control group and patients at stage I of the disease. The identified features indicate a decrease in the effectiveness of immune reactions of the monocytic link in stomach adenocarcinoma already in the early stages of the disease and can be used to detect early signs of immune disorders and optimize therapeutic approaches in this disease.